2022
DOI: 10.12688/f1000research.19931.5
|View full text |Cite
|
Sign up to set email alerts
|

Are adverse effects of cannabidiol (CBD) products caused by tetrahydrocannabinol (THC) contamination?

Abstract: Cannabidiol (CBD)-containing products are widely marketed as over the counter products, mostly as food supplements. Adverse effects reported in anecdotal consumer reports or during clinical studies were first assumed to be due to hydrolytic conversion of CBD to psychotropic Δ9-tetrahydrocannabinol (Δ9-THC) in the stomach after oral consumption. However, research of pure CBD solutions stored in simulated gastric juice or subjected to various storage conditions such as heat and light with specific liquid chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…This controversy has not been fully resolved yet, though it is generally accepted that conversion of CBD to Δ 8 -THC and/or Δ 9 -THC in vivo in amount sufficient to elicit any pharmacological action is unlikely. 85,86 The second step of the large scale manufacture of HHC is catalytic hydrogenation of the crude or purified cyclization product consisting of a mixture Δ 8 /Δ 9 -THC in various ratio (Figure 6). Hydrogenation of a "tetrahydrocannabinol" preparation to afford HHC of unspecified stereochemistry was first published in 1940.…”
Section: Synthesis Of Hhc Based On Cannabidiol or Hemp Extractmentioning
confidence: 99%
See 1 more Smart Citation
“…This controversy has not been fully resolved yet, though it is generally accepted that conversion of CBD to Δ 8 -THC and/or Δ 9 -THC in vivo in amount sufficient to elicit any pharmacological action is unlikely. 85,86 The second step of the large scale manufacture of HHC is catalytic hydrogenation of the crude or purified cyclization product consisting of a mixture Δ 8 /Δ 9 -THC in various ratio (Figure 6). Hydrogenation of a "tetrahydrocannabinol" preparation to afford HHC of unspecified stereochemistry was first published in 1940.…”
Section: Synthesis Of Hhc Based On Cannabidiol or Hemp Extractmentioning
confidence: 99%
“…The report of CBD being converted to Δ 9 ‐THC in artificial gastric juice in vitro 84 has generated scientific debate on whether orally administered CBD, which is non‐psychotropic, would undergo such a transformation into psychotropic cannabinoids in the acidic environment of the human gut. This controversy has not been fully resolved yet, though it is generally accepted that conversion of CBD to Δ 8 ‐THC and/or Δ 9 ‐THC in vivo in amount sufficient to elicit any pharmacological action is unlikely 85,86 …”
Section: Hexahydrocannabinolmentioning
confidence: 99%
“…A recent analysis of 293 cannabis products, mostly CBD oils, on the German market revealed that 10% of these products contained THC above the lowest observed adverse effect level, which was set at 2.5 mg/day [ 64 ].…”
Section: Cannabis Productsmentioning
confidence: 99%
“…Limited conversion of CBD to Δ9‐THC in the presence of acid has been suggested to occur in in vitro models (Merrick et al., 2016; Bonn‐Miller et al., 2017). However, there is no evidence that this transformation occurs in humans in vivo (Nahler et al., 2017; Lachenmeier et al., 2019; Golombek et al., 2020).…”
Section: Limitations and Uncertainties In Scientific Literaturementioning
confidence: 99%